1984
DOI: 10.1139/v84-339
|View full text |Cite
|
Sign up to set email alerts
|

Vinylogous nucleophilic catalysis. Tertiary amine promoted hydrolysis of 1-alkene-1-sulfonyl chlorides

Abstract: This paper is dedicated to Professor Paul de Mayo on the occasion of his 60th birthday JAMES FREDERICK KING, JOHN HENRY HILLHOUSE, and STANISLAW SKONIECZNY. Can. J. Chem. 62, 1977Chem. 62, (1984. We present evidence that the reactions of ethenesulfonyl chloride ( I ) and trcrt~s-l -propene-l -sulfonyl chloride (3) with water in the presence of pyridine, trimethylamine, and a number of other tertiary amines proceed primarily by way of an initial + vinylogous substitution reaction to form the cationic sulFne, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…As in the case of the corresponding reaction in water (12), this observation points strongly to a common pathway for the two reactions. For the aqueous system mentioned earlier it was possible to show, from appropriate labelling experiments, that essentially all of the products were formed via the sulfene (8) with no detectable interconversion between 1 and 9a.…”
Section: Initial Experiments and Related Worksupporting
confidence: 63%
See 3 more Smart Citations
“…As in the case of the corresponding reaction in water (12), this observation points strongly to a common pathway for the two reactions. For the aqueous system mentioned earlier it was possible to show, from appropriate labelling experiments, that essentially all of the products were formed via the sulfene (8) with no detectable interconversion between 1 and 9a.…”
Section: Initial Experiments and Related Worksupporting
confidence: 63%
“…Instrumentation, methods, and provenance of most of the starting materials and comparison compounds have been previously described (2,12,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was therefore with considerable interest that we noted two reports of two quite different reactions which in each case might reasonably have been expected to yield 2-(phiny1thio)-ethanesulfonyl chloride ( l ) , but which describe instead only the identification of the formal desulfonylation product, 2-(phenylthio)ethyl chloride (2). In the first of these papers Kandror and Freidlina reported that reaction of benzenethiol (3) and ethenesulfonyl chloride (4) gives 2, and, to account for this product, put forward a free radical rearrangement mechanism involving migration of a chlorine atom from sulfur to carbon followed by loss of sulfur dioxide (7).…”
mentioning
confidence: 99%